Trade attitudes in Latin America: Evidence from a multi-country survey experiment - Marisol Rodríguez Chatruc; Ernesto Hugo Stein; Razvan Vlaicu (Inter-American Development Bank (IDB), 2019)
This paper examines individual-level support for trade liberalization, relates it to beliefs about trade, and measures its sensitivity to positive and negative framing. The data come from the 2018 Latinobarometro survey of eighteen countries, in which the authors embedded a survey experiment to study framing effects. It is found that respondents are generally favorable to increased trade with other countries, based on perceived trade benefits to employment, prices, and product variety. Support for trade is unaffected by positive framing but is highly sensitive downward to employment loss framing. Positive framing does shift upward respondent beliefs that trade increases product variety and reduces prices, but also raises concerns about low wages. Negative framing substantially reduces the prevailing beliefs that trade is associated with high employment, and there is no offsetting effect on the consumption side. Trade support levels and sensitivity display heterogeneity across education levels consistent with skill-based theories of trade, as well as interesting country, age, gender, and income heterogeneity.
Keywords: F13; D72; 330; Trade liberalization; Trade preferences; Trade beliefs; Survey experiment; Framing